Method and substance of Islamic economics revisited - Mohd Yusop, Mohd Mahyudi; Abdul Aziz, Enizahura (King Abdul Aziz University, 2018)
This paper provides fresh deliberations on the method and substance of Islamic economics by relying on the structure and contents of Nienhaus (2013). Introspective arguments are furnished to soundly argue that Islamic economics is still a widely disregarded field; it is an integrated science; its normative dimension is not a deterrent element; ‘Islamic economics light’ studies are one inseparable part of the discipline; and Islamic economics is a political economy. On the aforementioned issues, we essentially make further elaborations on our Islamic economics definition, ‘Qur’ānic framework’, Islamic epistemology and Islamic criteria originating from Mahyudi and Abdul Aziz (2017). The elaborations are extended to expound on their positive impact to the Islamization of knowledge agenda. We also utilize Bakar (2016) to reduce the observed tension between Sharīʿah scholars and Islamic economists that is triggered by issues surrounding legal form and economic reasoning of Islamic banking and finance products. Armed with the latest views over some foundational topics in the philosophy of Islamic economics science, our discussions proffer some guiding points on the proper conduct of Islamic economists in engaging with conventional economists and Islamic jurisprudence experts.